RADIONUCLIDE DIAGNOSTICS OF BONE METASTASES IN PATIENTS WITH PROSTATE CANCER - E. Portnyaga; N. Skokova; M. Tkachenko; G. Romanenko; A. Makarenko (Bogomolets National Medical University, 2016)
The article shows the possibilities of bone scintigraphy to identify and to dynamic supervise the secondary affected skeleton in patients with prostate cancer. According to our observations the bone scintigraphy is quite informative method for early detection of bone metastases in patients with prostate cancer; it allows up to 12 months earlier than other imaging methods to detect metastases in bone and qualitatively estimate the degree of bone damage. Patients with prostate cancer should be required to conduct bone scintigraphy to exclude bone metastases annually for 5 years dispensary observation or when complaints occur.